2022
DOI: 10.4028/p-7cwhpb
|View full text |Cite
|
Sign up to set email alerts
|

Fine Blanking Limits of Manganese-Boron-Steel in Fine Blanking Compared to Tempered Steel with Variation of Sheet Metal Temperature

Abstract: Fine blanking is a key technology for the near-net-shape production of sheet metal components. It is often used in combination with processes such as deep drawing. With increasing environmental requirements, the processing of materials with lightweight construction potential is becoming more and more important. A group of materials with high potential for lightweight construction, not only due to their suitability for hot stamping, is the group of manganese-boron steels. The fine blanking properties of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The process forces were evaluated depending on the sheet metal temperature and a good fine blanking capability of 40MnB4 was confirmed. Moreover, results showed that process forces and product quality were comparable to 42CrMo4 steel [7].…”
Section: Warm Assisted Fine Blankingmentioning
confidence: 82%
“…The process forces were evaluated depending on the sheet metal temperature and a good fine blanking capability of 40MnB4 was confirmed. Moreover, results showed that process forces and product quality were comparable to 42CrMo4 steel [7].…”
Section: Warm Assisted Fine Blankingmentioning
confidence: 82%